THE ROLE OF THE MAHKOTA WITNESSES IN PROOFING THE CRIMINAL ACTION OF NARCOTICS IN THE MAKASSAR STATE COURT - Sulfiati; Kamri Ahmad; Abdul Agis (Meraja journal, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal